APLIKASI INDOLE-3-BUTYRIC ACID DAN NAPHTHALENE ACETIC ACID PADA BERBAGAI BAHAN SETEK JAMBU MADU DELI HIJAU DENGAN SISTEM HIDROPONIK NFT - Rizka Novi Sesanti; Hilman Hidayat; Sismanto Sismanto (Jurnal WACANA PERTANIAN, 2018)
This research is about application IBA and NAA with some cutting materials of “Madu Deli Hijau” water apple using NFT hydroponic system was aim to study the growth of water apple’s cuttings was treated by IBA and NAA 500 ppm and study the best kind of cutting materials of water apple that can growth the most.  This research was conducted using completely randomized design in two factors.  The first was consisted of 7 treatments; control (without Auxin), IBA 500 ppm, and NAA 500 ppm. The second was consisted of 4 treatments; woody branch (hardwood), semi woody (semi hardwood), and soft branch, softwood, and shoots. The results showed that the added auxin in the form of IBA and NAA 500 ppm can increase the success of madu deli hijau water apple cuttings and the cuttings from the shoots are the best for the success of madu deli hijau water apple in NFT hydroponic system.